Construction of the Wali Pitu’s Sacredness and Islamic Veneration in Balinese Hindu Civilization - Amin Tohari (Islam Realitas: Journal of Islamic and Social Studies, 2021)
This article explains the Wali Pitu (the seven saints) as a new form of veneration dynamics in Indonesia, which was built by the sacredness of Bali as the heart of Hindu culture in Indonesia. This phenomenon is unique and interesting, because the seven tombs of Muslim saints are venerated by Hindus of the region. This study uses a qualitative approach with the case-study method, extracting data as documentation from the notes of Toyyib Zaen Arifin during the expedition to search the seven graves, and interviews with members of the Manaqib al-Jamali, guidance, organizers and religious tourism congregations, as well as several caretakers of the tombs. This article describes the sacred construction of the discovery of the seven sainthoods tombs and their cults and their dynamics as a new form of the veneration of saints in Indonesia, one that differs from the other forms of veneration in Java which has been deeply rooted for a long time, such as the Wali Songo (the nine saints). Artikel ini berupaya menjelaskan Wali Pitu (tujuh wali) sebagai bentuk baru dinamika venerasi di Indonesia yang dibangun oleh sakralitas Bali sebagai jantung peradaban Hindu. Fenomena ini sangat unik dan menarik dimana kedua korpus yang diteliti sangat kontradiktif namun menjadi sebuah realitas nyata, dimana tujuh makam wali Muslim ditemukan di Bali sebagai jantung peradaban Hindu. Menggunakan pendekatan kualitatif dengan metode studi kasus, penggalian data berupa dokumentasi dari hasil catatan Toyyib Zaen Arifin selama ekspedisi pencarian tujuh makam wali, dan wawancara kepada anggota manaqib al-Jamali, pembimbing, penyelenggara dan jama’ah wisata religi, serta beberapa juru kunci makam Wali Pitu. Artikel ini menjelaskan konstruksi sakralitas atas penemuan tujuh makam wali dan pengkultusannya serta dinamikanya sebagai wujud baru venerasi orang suci di Indonesia yang berbeda dengan venerasi sebelumnya di Jawa yang sudah mengakar kuat sejak lama (Wali Songo).